2020
DOI: 10.1002/anie.202002240
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Integrated Photoelectrochemical Reactor for H2 Production from Water Attains a Solar‐to‐Hydrogen Efficiency of 18 % at 15 Suns and 13 % at 207 Suns

Abstract: The major challenge in solar water splitting to H2 and O2 is in making a stable and affordable system for large‐scale applications. We have designed, fabricated, and tested a photoelectrochemical reactor characterized as follows: 1) it comprises an integrated device to reduce the balance of the system cost, 2) it utilizes concentrated sunlight to reduce the photoabsorber cost, and 3) it employs and alkaline electrolyte to reduce catalyst cost and eliminate external thermal management needs. The system consists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…integrated a triple‐junction GaInP/GaInAs/Ge photovoltaic within a PEC reactor. [ 161,162 ] Ni foil was affixed to the Ge side of the photovoltaic, which drove the water oxidation reaction in solution. The GaInP side was wired to a Pt‐coated Ti mesh, which drove the water reduction reaction.…”
Section: Materials Choice For Pec Water Splittingmentioning
confidence: 99%
“…integrated a triple‐junction GaInP/GaInAs/Ge photovoltaic within a PEC reactor. [ 161,162 ] Ni foil was affixed to the Ge side of the photovoltaic, which drove the water oxidation reaction in solution. The GaInP side was wired to a Pt‐coated Ti mesh, which drove the water reduction reaction.…”
Section: Materials Choice For Pec Water Splittingmentioning
confidence: 99%
“…Producing green hydrogen at a cost that is competitive with fossil fuel-derived hydrogen is one of the major challenges for transitioning to a hydrogen economy. [1] There are promising technologies for converting solar energy and water to hydrogen, such as coupling of photovoltaic and electrolysis (PV+E), [2] photoelectrochemical (PEC) [3,4] and (particulate) photocatalytic (PC) [5] water splitting (see Figure 1). These technologies, however, cannot currently produce hydrogen at a cost that is competitive with hydrogen derived from steam reforming.…”
Section: Main Textmentioning
confidence: 99%
“…Irradiation of the PEC cells leads to hydrogen and oxygen production on opposites sides of cell, so that pure hydrogen can be obtained (see Figure 1, PEC). State-of-the-art properties of the PEC cells are based on devices by Kistler et al [3] and Khan et al [4] using a III-V absorber. The layout of the hydrogen production plant is based on Pinaud et al (type 4 -PEC).…”
Section: Hydrogen Production Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability issues related to the back side of the cells has been addressed as shown in Figure 2 . It was found that a Ni foil connected to the back side protects it from corrosion and depending on its thickness and extracted current this can extend to many years (more details can be found in Khan et al [ 63 ] ). At present, the practice is to protect the front side (the side receiving light) with a poly(methyl methacrylate) (PMMA) window and extract the generated electrons toward a cathode (the loss is ≈6% of the photons’ flux in this case).…”
Section: Photocatalytic (Pc) and Photoelectrocatalytic (Pec) Water Spmentioning
confidence: 99%